KEBIJAKAN ORDE BARU VERSUS PENCURIAN KOREK API - Khairul Tri Anjani (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Juvenile delinquency in Jakarta Theft of Lighters in Student Boarding Areas 1965-1998. This study aims to determine the juvenile delinquency in Jakarta in the theft of matches in the 1965 student boarding area, besides that the authors also expect readers to understand juvenile delinquency in Jakarta. Research uses historical research methods. The method used is heuristics, criticism / verification, interpretation and historical writing. The results of the study understood the initial program of economic and education policy during the New Order government, could understand juvenile delinquency in the student settlement environment during the New Order government, outline match theft and its continued development until the end of the new order government.